PENERAPAN MEDIA PEMBELAJARAN ADOBE FLASH CS 6 DI KELAS X SMA KAMPUS FKIP UHN PEMATANGSIANTAR - Siregar, Junifer (Universitas Negeri Medan, 2020)
Abstract Abstract: Learning with the use of instructional media that is not appropriate is still often the case, so learning is not in line with expectations. This is what happened at Pematangsiantar FKIP UHN Senior High School. This article aims to provide an overview of the use of Adobe Flash CS 6 media in the learning process at the FKIP UHN Pematangsiantar Campus. Adobe Flash CS 6 is used for making animations that are equipped with attractive displays in the form of applications to design and create interactive learning media. Student learning outcomes in writing the paragraph description at the pretest stage of 30 students 11 declared complete and 19 students declared incomplete with a mean score of 58.02 and at the post-test stage of 30 students 26 students declared complete 4 students declared incomplete with an average value 83, 35. This proves that learning media by using Adobe Flash CS 6 can improve learning outcomes in writing paragraph descriptions for grade X students of the FKIP UHN Pematangsiantar campus. Keywords: Learning Media, Adobe Flash CS 6, Paragraph Description